Influence of Pre-Treatment and Artificial Aging on the Retention of 3D-Printed Permanent Composite Crowns - Tobias Graf; Kurt-Jürgen Erdelt; Jan-Frederik Güth; Daniel Edelhoff; Oliver Schubert; Josef Schweiger (Biomedicines, 2022)
The aim of this in vitro study is to investigate the bonding properties of a 3D-printable permanent composite material in comparison to milled composite materials. The tested materials are 3D-printed BEGO VarseoSmile Crown plus (VA1_ab, VA1_nt, VA2_ab, VA2_nt), Vita Enamic (EN1, EN2), and 3M Lava Ultimate (UL1, UL2) (N = 64; n = 8). For this purpose, all crowns are luted to polymer tooth stumps #46 (FDI) using dual-curing luting composite, strictly according to the manufacturer’s instructions. VA1_ab and VA2_ab are additionally airborne-particle abraded. 4 groups (VA2_ab, VA2_nt, EN2, UL2) are artificially aged (1,200,000 cycles, 50 N, 10,000 thermocycles), whereby no specimen has failed. All 64 specimens undergo pull-off testing until retention loss. The mean forces of retention-loss is 786.6 ± 137.6 N (VA1_nt, *), 988.6 ± 212.1 N (VA2_nt, *, Ɨ), 1223.8 ± 119.2 N (VA1_ab, Ɨ, ǂ), 1051.9 ± 107.2 N (VA2_ab, *, Ɨ), 1185.9 ± 211.8 N (EN1, Ɨ, ǂ), 1485.0 ± 198.2 N EN2, ǂ), 1533.8 ± 42.4 N (UL1, ǂ), and 1521.8 ± 343.4 N (UL2, ǂ) (one-way ANOVA (Scheffé method); p < 0.05; *, Ɨ, ǂ: group distribution). No characteristic failure modes can be detected. In conclusion, all of the pull-off forces reflect retention values that seem to be sufficiently high for clinical use. Additional airborne-particle abrasion of VA does not result in significantly better retention but can be recommended.